2019
DOI: 10.1590/abd1806-4841.20198166
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous collagenous vasculopathy: light and transmission electron microscopy

Abstract: Cutaneous collagenous vasculopathy is a rare acquired idiopathic microangiopathy characterized by progressive development of diffuse asymptomatic telangiectasias and histologically by accumulation of collagen type IV around the affected vessels. It is diagnosed by its clinical history, confirmed by light microscopy with collagen-specific immunostaining. We report a case of a patient with extensive acquired telangiectasias on the left arm, clinically resembling unilateral nevoid telangiectasia. Dilated blood ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 8 publications
(9 reference statements)
0
20
0
3
Order By: Relevance
“…Veil cells and Luse bodies (abnormal collagen) with focal endothelial damage can also be seen on electron microscopy. 4 Treatment options are limited. Pulsed dye laser therapy has been suggested and was successful in one case, warranting further exploration.…”
Section: Images In…mentioning
confidence: 99%
“…Veil cells and Luse bodies (abnormal collagen) with focal endothelial damage can also be seen on electron microscopy. 4 Treatment options are limited. Pulsed dye laser therapy has been suggested and was successful in one case, warranting further exploration.…”
Section: Images In…mentioning
confidence: 99%
“…It has been suggested that endothelial cell injury, regardless of the mechanism, leading to endothelial cell denudement is a stimulus to microvascular basement membrane zone thickening 7 . The multiple laminations of the reduplicated basement membrane zones can be highlighted by Type IV collagen and PAS stains 7–11 …”
Section: Discussionmentioning
confidence: 99%
“…7 The multiple laminations of the reduplicated basement membrane zones can be highlighted by Type IV collagen and PAS stains. [7][8][9][10][11] Lipoid proteinosis exhibits a similar pattern of thickened vessel walls; however, its basis is not one of basement membrane zone reduplication as a sequela of antecedent endothelial cell injury.…”
Section: Discussionmentioning
confidence: 99%
“…В одном случае первые телеангиэктазии появились на коже груди [8], в другом на коже верхних конечностей [17]. В некоторых случаях телеангиэктазии присутствовали только на коже одной ноги [5], или руки [15], или поражали только оба предплечья [5].…”
Section: актуальностьunclassified